Modeling of the Aorta: Complexities and Inadequacies - Rajagopal, Kumbakonam R.; Rajagopal, Keshava (AORTA, 2020)
The aorta is a very complex organ comprising three layers, consisting of four kinds of tissues. It is an anisotropic, inhomogeneous, multiconstituent, and living organ that presents both a formidable challenge and a tremendous opportunity to a modeler to mathematically characterize its structure. Unfortunately, even the most sophisticated models in vogue do not faithfully take into consideration its various complexities, falling very short of putting into place a reasonable model, as they ignore many of the quintessential features that need to be taken into account. In this article, we address the various features that need to be taken into account to develop a meaningful model of the aorta.
Keywords: aorta; viscoelasticity; anisotropy; inhomogeneity; mixture; fluid–solid interaction